Government strategies in confronting climate change to ensure the assurance of food security in Malaysia - Damin, Zahrul Akmal; Mohamed, Ahmad Martadha; Ani, Fauziah; Jaes, Lutfan; Kamri, Khairol Anuar; Johar, Siti Sarawati; Kamarul Azmi, Kamarul Azam (Science Publishing Corporation (SPC), 2018)
Recently, food security issues have gained huge concern by the government due to unstable climate change. It seems there is a need for the government to formulate a strategy in order to enhance the security of food by confronting climate change, which will be able to not only lower production of food, but also to destroy food crops. This research intends to identify the strategies implemented by the government to ensure the security of food in facing climate change. Based on qualitative approach and design content analysis, 20 documents of annual budget presentation from 1994 to 2013 have been selected in order to gather data. Obtained data were then analysed to see the influence of climate change on food security, especially government‟s strategy in addressing climate change to ensure the assurance of food security. From the result of the analysed data, we found that there are five main themes, resulting from the government‟s strategies which are (i) preservation and conversation; 31.96%, (ii) risk management; 21.31%, (iii) financing fund; 18.03%, (iv) law enforcement; 16.40%, and (v) education and awareness; 12.30%. It is hoped that the result of this research can help policy makers to create and improve strategies to deal with climate change, while at the same time protecting the country from any unforeseen circumstances related to food security issues.